Experiences of using a digital type 2 diabetes prevention application designed to support women with previous gestational diabetes - Winifred Ekezie; Helen Dallosso; Ponnusamy Saravanan; Kamlesh Khunti; Michelle Hadjiconstantinou (BMC, 2021)
Abstract Background Gestational diabetes mellitus (GDM) is diagnosed during pregnancy, and women with a history of GDM are at a higher risk of developing type 2 diabetes mellitus (T2DM). Prevention strategies focused on lifestyle modification help to reduce long-term complications. Self-management technology-based interventions can support behaviour change and diabetes control. The Baby Steps programme, a randomised controlled trial intervention offering group education and access to a mobile web application, was evaluated to explore user experience of the app and barriers and facilitators to app usability. Methods Ten semi-structured interviews and four focus group discussions were conducted with 23 trial participants between 2018 and 2019. Interviews and focus group discussions were audiotaped, transcribed and independently analysed. The analysis was informed by thematic analysis, with the use of the Nvivo 12 software. Results Themes identified were: (1) GDM and post-pregnancy support from healthcare services; (2) Impact of Baby Steps app on lifestyle changes; (3) Facilitators and barriers to the usability of the Baby Steps app. The Baby Steps app served as a motivator for increasing self-management activities and a tool for monitoring progress. Peer support and increased awareness of GDM and T2DM enhanced engagement with the app, while poor awareness of all the components of the app and low technical skills contributed to low usability. Conclusions This study documents experiences from existing GDM support, user experiences from using the Baby Steps app, and the barriers and facilitators to app usability. The app was both a motivational and a monitoring tool for GDM self-management and T2DM prevention. Peer support was a key trait for enhanced engagement, while barriers were low technical skills and poor awareness of the app components. A digital app, such as the Baby Steps app, could strengthen existing face-to-face support for the prevention of T2DM. The results also have wider implications for digital support technologies for all self-management interventions. Further research on the effect of specific components of apps will be required to better understand the long term impact of apps and digital interventions on self-management behaviours and outcomes. Trial registration ISRCTN, ISRCTN17299860 . Registered on 5 April 2017.